Predicting the Adoption of Mobile Business Applications by Culinary SMEs in Indonesia - Nugroho Hardiyanto; Wahyu Rafdinal; Mohammad Rizal Gaffar (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Objective: This study aims to analyze the adoption of mobile business applications by culinary SMEs in Indonesia using the extended TAM (technology acceptance model). The extended TAM used in this study uses additional variables such as subjective norms, self-efficacy, and facilitating conditions, which the previous study used these variables in the context of technology adoption. Research Design & Methods: The sample used was 424 respondents of culinary SMEs in Indonesia. Data collection was found using an online questionnaire, meanwhile, for data processing using the PLS-SEM method. Findings: The results show that culinary SMEs will use a mobile business application if the application is useful and easy to use. In addition, they also need to be encouraged by social environmental factors (subjective norms), self-confidence to use the application (self-efficacy), and supporting facilities conditions. Implications & Recommendations: Theoretically, this research uses extended TAM which has been used previously but in a different context, namely the adoption of mobile business applications. Practically, this research will provide insight for application development companies to create mobile business applications that can be well adopted by culinary SMEs. Contribution & Value Added: This study is the first to empirically employ the TAM, subjective norms, self-confidence, self-efficacy, and facilitating conditions in analyzing the adoption of mobile business applications by culinary SMEs.